Analysis of Internal Control on Bai' Taqsith Financing in Sharia Cooperatives - Andriani; Aprillita, Rizky (CV. Jala Berkat Abadi, 2023)
This study aims to analyze the application of the internal control system in bai' taqsith financing activities at the Ammar Madani Ummah Sharia Consumer Cooperative by discussing in detail the following elements of internal control: elements of separation of duties and responsibilities, authority systems and recording procedures, healthy practices and employees of appropriate quality. This research is a type of case study research with a qualitative approach with the type of data used, namely primary data and secondary data. Data collection methods through observation, interviews, documentation and literature studies. The results showed that the internal control system applied to the Ammar Madani Ummah Sharia Consumer Cooperative was quite good and fulfilled the elements of internal control in the form of elements of separation of duties and responsibilities, authority systems and recording procedures, healthy practices and employees of appropriate quality. However, there are several weaknesses that occur, namely the task trap by the service function which doubles into the cashier function. The occurrence of inefficiencies in the procedures carried out due to data re-input. Authorization systems are less reliable, usually only through whatsapp media.